The validity of animal models to explore the pathogenic role of the complement system in multiple sclerosis: A review - Saez-Calveras, Nil; Brewster, Amy L.; Stuve, Olaf (Frontiers in Molecular Neuroscience, 2022)
Animal models of multiple sclerosis (MS) have been extensively used to characterize the disease mechanisms in MS, as well as to identify potential pharmacologic targets for this condition. In recent years, the immune complement system has gained increased attention as an important effector in the pathogenesis of MS. Evidence from histological, serum, and CSF studies of patients supports an involvement of complement in both relapsing-remitting and progressive MS. In this review, we discuss the history and advances made on the use of MS animal models to profile the effects of the complement system in this condition. The first studies that explored the complement system in the context of MS used cobra venom factor (CVF) as a complement depleting agent in experimental autoimmune encephalomyelitis (EAE) Lewis rats. Since then, multiple mice and rat models of MS have revealed a role of C3 and the alternative complement cascade in the opsonization and phagocytosis of myelin by microglia and myeloid cells. Studies using viral vectors, genetic knockouts and pharmacologic complement inhibitors have also shown an effect of complement in synaptic loss. Antibody-mediated EAE models have revealed an involvement of the C1 complex and the classical complement as an effector of the humoral response in this disease. C1q itself may also be involved in modulating microglia activation and oligodendrocyte differentiation in these animals. In addition, animal and in vitro models have revealed that multiple complement factors may act as modulators of both the innate and adaptive immune responses. Finally, evidence gathered from mice models suggests that the membrane attack complex (MAC) may even exert protective roles in the chronic stages of EAE. Overall, this review summarizes the importance of MS animal models to better characterize the role of the complement system and guide future therapeutic approaches in this condition.